Garmian on the ancient cross-roads of the regional and international trade caravans - Marf, Asst.Prof.Dr. Dlshad Aziz; Abdullah, Asst.L. Rezan Qadir (Sulaimani Journal for Humanities, 2025)
Garmian was situated on the ancient roads, serving as sub-roads for regional and international trade caravans. The region held significant geographical importance as it was where the fertile plains of Mesopotamia met the Zagros Mountains. This led to Garmian becoming a hub for local and international merchants from the time of agricultural villages in the Prehistoric periods to the eras of cities, states, and empires. This paper addresses research questions regarding the role of the Garmian region in regional and international trade. What goods were produced and traded in this area? What was the region's role in trade between the kingdoms and states of Mesopotamia and the ancient Zagros mountains, as well as in international trade along the Khorasan Road and the Silk Road? This study relies on archaeological evidence, cuneiform, and classical records.
Keywords: Garmian; Caravanserai Trade; Silk Road; Khorasan Road